9-Arylimino noscapinoids as potent tubulin binding anticancer agent: chemical synthesis and cellular evaluation against breast tumour cells. Issue 4 (3rd April 2021) - Patel, A.K.; Meher, R.K.; Nagireddy, P.K.; Pragyandipta, P.; Pedapati, R.K.; Kantevari, S.; Naik, P.K.
ABSTRACT: A library of 9-arylimino derivatives of noscapine was developed by coupling of Schiff base containing imine groups. Virtual screening using molecular docking with tubulin revealed three molecules, 12–14 that bind with high affinity. An improved predicted free energy of binding (FEB) of −5.390, −6.506 and −6.679 kcal/mol for the molecules 12–14 was found compared to noscapine (−5.135 kcal/mol). Furthermore, molecular dynamics simulation in combination with Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) revealed robust binding free energy of −166.03, −169.75 and −170.63 kcal/mol for the molecules 12, 13 and 14, respectively. These derivatives were strategically synthesized and experimentally validated for their anticancer activity. Tubulin binding assay revealed substantial binding of molecules 12–14 with purified tubulin. Further, their anticancer activity was demonstrated using two cancer cell lines (MCF-7 and MDAMB-231) and a panel of primary breast tumour cells. All these derivatives inhibited cellular proliferation in all the cancer cells that ranged between 30.1 and 5.8 µM, which is 1.7 to 7.52 fold lower than that of noscapine. Further, these novel derivatives arrest cell cycle in the G2/M-phase followed by induction of apoptosis. Thus, 9-arylimino noscapinoids 12–14 have a great potential to be a novel therapeutic agent for breast cancers.